Analisa Kadar Protein Pada Teripang (Holothuria argus) Terhadap Lama Perebusan - Baterun Kunsah (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2017)
ABSTRACTProtein is the most important nutrients in the body, which serves as a new network-forming and maintaining or repairing worn tissue. Protein cucumbers reach 82% of his body. However, the protein can undergo denaturation when heated. Formulation of the research problem is whether there was an effect on long boiling sea cucumbers (Holothuria argus) the protein content. The research objective was to determine whether there is a long effect on the boiling sea cucumbers (Holothuria argus) the protein content.This type of research is experimental. The study population was all kinds of sea cucumbers are caught by fishermen in Kel.Sukolilo Kec.Bulak Surabaya. The research sample is sea cucumber Holothuria argus species caught by fishermen in Kel.Sukolilo Kec.Bulak Surabaya. Research using the 5 treatments with 5 repetitions. Criteria longer boiling is P1 (0 min / control), P2 (15 min), P3 (30 minutes), P4 (45 minutes), and P5 (60 minutes).Data examined protein levels by means of laboratory tests. Based on the laboratory results obtained average amount of 16.948% protein content in boiling 0 minutes, 13.068% in 15 minutes, 11.986% at 30 minutes, 10.652% at 45 minutes, and 8.732% in boiling water 60 minutes.Test results are then tested the statistical ANOVA showed significant values where 0.000 <0.05 (α). It can be concluded that there is a long effect on the boiling sea cucumbers (Holothuria argus) the protein content.Keywords: Sea Cucumber & Protein Levels